A guide to health - Gandhi, M. (Brazilian Journal of Implantology and Health Sciences, 2019)
Having great health is a desire we all have. We can say that health is our greatest asset! It is not necessary to list the multitude of advantages that good health brings us. And it is worth noting that in order to have good health, basic care that is relatively easy to be experienced is necessary. Check out some of them below and make an assessment: do you take the most basic care to have good health?